2021
DOI: 10.3390/d13100494
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Amplicon Sequencing Data of the Iron Quadrangle Ferruginous Caves (Brazil) Shows the Importance of Conserving This Singular and Threatened Geosystem

Abstract: The Iron Quadrangle (IQ) is one of the main iron ore producing regions of the world. The exploitation of its reserves jeopardizes the high biological endemism associated with this region. This work aimed to understand the diversity and bacterial potential associated with IQ caves. Floor and ceiling samples of seven ferruginous caves and one quartzite cave were collected, and their microbial relative abundance and diversity were established by 16S rRNA gene amplicon sequencing data. The results showed that ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 111 publications
(121 reference statements)
0
1
0
1
Order By: Relevance
“…According to literature reports, the dominant phyla identified in caves are Proteobacteria and Actinobacteria, characterized by Gram-negative and Gram-positive bacteria, respectively [27,28], with proteobacteria being detected mainly through molecular tools, while actinobacteria represent most culture-dependent isolates [29]. However, Lemes et al (2021) [30] identified that the phylum Acidobacteria (Gram-negative) was the most abundant in the Canga caves analyzed in the Iron Quadrangle, followed by Proteobacteria and Actinobacteria.…”
Section: Figure 6: Dendrogram Of the Hierarchical Cluster Analysis (W...mentioning
confidence: 99%
“…According to literature reports, the dominant phyla identified in caves are Proteobacteria and Actinobacteria, characterized by Gram-negative and Gram-positive bacteria, respectively [27,28], with proteobacteria being detected mainly through molecular tools, while actinobacteria represent most culture-dependent isolates [29]. However, Lemes et al (2021) [30] identified that the phylum Acidobacteria (Gram-negative) was the most abundant in the Canga caves analyzed in the Iron Quadrangle, followed by Proteobacteria and Actinobacteria.…”
Section: Figure 6: Dendrogram Of the Hierarchical Cluster Analysis (W...mentioning
confidence: 99%
“…Due to the enormous metabolic diversity, microorganisms actively participate in all biogeochemical cycles and perform the function of recycling much of the matter in the biosphere (Gaylarde, 2005). The abiotic and biotic factors of the environment directly influence the microbial community (Gaylarde, 2005), microbiana (Gaylarde, 2005), o que torna ainda mais importante o conhecimento das condições ambientais para um completo conhecimento sobre a composição microbiana e seu funcionamento metabólico em diferentes ambientes (Lemes, 2018;Lemes, 2021).…”
Section: Microbiota Importance In An Ecological Contextunclassified
“…which makes it even more important to know the environmental conditions for a complete understanding of the microbial composition and its metabolic functioning in different environments (Lemes, 2018;Lemes, 2021).…”
Section: Potencial Biotecnológico Dos Microrganismosmentioning
confidence: 99%